Synthesis and characterisation of hydrophobic catalyst – Cs salt of 12-phosphotungstic acid functionalised dealuminated usy for the esterification of acrylic acid with butanol - Kah Hoay, Tan (2015)
Research and development work of acrylic acid (AA) recovery from petrochemicals industries effluent has been extensively carried out to minimize the production cost as well as to save the environment from any impacts of its high COD level. Esterification in reactive distillation column is one of the promising methods to recover the AA from the effluent. A hydrophobic heterogeneous catalyst is required to treat the dilute AA in RD column. In this work, heterogeneous hydrophobic catalyst -the Cesium (Cs) Salt of Phosphotungstic Acid (PW) Functionalised Dealuminated Ultra-Stable Y Zeolite (DUSY) with various loadings and amount of Cs was synthesised through impregnation method for the esterification reaction of AA with butanol. The catalyst was characterised using X-Ray Diffraction and X-Ray Fluorescence analysis method. The DUSY supported Cs salt of PW with 0.5 mole of Cs/mole of salt showed highest activity at 50%AA dilute system (23%yield & 27% conversion). It was found that the highest yield of 26% and conversion of 32% can be attained in the esterification reaction catalysed by the catalyst with 40% loading of Cs salt of PW (0.5 mole of Cs/1 mole of salt). Leaching test which performed using UV-Vis Spectrophotometer showed that the water tolerance ability decreased with increasing loading of % Cs0.5PW. The developed catalyst is potential to be employed in the esterification of dilute AA with butanol, aiming to recover the AA from the petrochemical waste effluent.